2019
DOI: 10.3390/math7030247
|View full text |Cite
|
Sign up to set email alerts
|

3D Visualization through the Hologram for the Learning of Area and Volume Concepts

Abstract: This study aims to implement and evaluate a methodological proposal using the hologram as a teaching medium for the learning of concepts related to areas and volumes of geometrical bodies. The study has been carried out with a sample of 78 students in the third year of secondary education from a privately-owned but state-funded school in Madrid. Thirty-five students who have been taught traditionally formed the control group, and 43 formed the experimental group in which the methodology was implemented. To eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
2
10
0
2
Order By: Relevance
“…∆(x) r m m ∆ 1 (x) = (sin 2 x − x 2 + 1) 2 1.404491648215341 2 ∆ 2 (x) = (x − 5) 3 5 3 ∆ 3 (x) = (e x 2 +7x−30 − 1) 4 3 4 ∆ 4 (x) = ((x − 1) 3 − 1) 6 2 6 ∆ 5 (x) = (e x + x − 20) 2 2.842438953784447 2 ∆ 6 (x) = (cosx − x) 4 0.739085133215161 4 ∆ 7 (x) = (x 2 − e x − 3x + 2) 3 0.257530285439860 3 ∆ 8 (x) = (x 2 − 16) 3 4 3 ∆ 9 (x) = (x 3 − 12x 2 + 44x − 48) 3 2 3 ∆ 10 (x) = x 3 sin4x 0 4…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…∆(x) r m m ∆ 1 (x) = (sin 2 x − x 2 + 1) 2 1.404491648215341 2 ∆ 2 (x) = (x − 5) 3 5 3 ∆ 3 (x) = (e x 2 +7x−30 − 1) 4 3 4 ∆ 4 (x) = ((x − 1) 3 − 1) 6 2 6 ∆ 5 (x) = (e x + x − 20) 2 2.842438953784447 2 ∆ 6 (x) = (cosx − x) 4 0.739085133215161 4 ∆ 7 (x) = (x 2 − e x − 3x + 2) 3 0.257530285439860 3 ∆ 8 (x) = (x 2 − 16) 3 4 3 ∆ 9 (x) = (x 3 − 12x 2 + 44x − 48) 3 2 3 ∆ 10 (x) = x 3 sin4x 0 4…”
Section: Numerical Resultsmentioning
confidence: 99%
“…In this paper, we present a study on iterative methods that can be used in postgraduate studies in order to teach them. Many problems of numerous disciplines such as applied sciences, scientific computing, and engineering [3][4][5][6][7] can be converted to mathematical expressions. Some of them can be transformed to an equation of the following form:…”
Section: Introductionmentioning
confidence: 99%
“…Today there are many specimens of malware, as mentioned above, that use multiple attack techniques and vectors and are conducted stealthily to avoid detection, in order to retain unnoticed control over targeted systems for long periods of time [2]. On the other hand, in recent decades with the new educational technologies and the growth of the Massive Open Online Course (MOOCs) [3][4][5][6][7][8] there are new opportunities for this kind of malware to 'catch' new objectives and personal data which can be really important.…”
Section: Introductionmentioning
confidence: 99%
“…Possibilities for AR applications in research are also promising. Different studies had demonstrated the AR usefulness for increasing the student motivation, as well as for enhancing a wide variety of learning domains [3,7,[10][11][12][13][14][15][16]. In particular, the meta-analysis provided by [4] among JCR publications on the state of AR applications in the Education field, concludes that there is a increasing trend, specially during the last 4 years, on the Science and Humanities & Arts areas.…”
Section: Introductionmentioning
confidence: 99%